Blockchain technology and internet of things: review, challenge and security concern - Mahmood Subhy Mahmood; Najla Badie Al Dabagh (Institute of Advanced Engineering and Science, 2023)
Blockchain (BC) has received high attention from many researchers recently because it has decentralization, trusted auditability, and transparency as its main properties. BC has contributed fundamentally to the development of applications like cryptocurrencies, health care, the internet of things (IoT), and so on. The IoT is envisioned to include billions of pervasive and mission-critical sensors and actuators connected to the internet. This network of smart devices is expected to generate and have access to vast amounts of information, creating unique opportunities for new applications, but significant security and privacy issues emerge concurrently because it does not contain robust security systems. BC provides many services like privacy, security, and provenance to the systems that depends on. This research includes analyzing and a comprehensive review of BC technologies. Moreover, the proposed solutions in academia with the methodologies that used to integrate blockchain with IoT are presented. Also, the types of attacks on blockchain are collected and classified. Furthermore, the main contributions and challenges that are included in the literature are explored, then the relevant recommendations for solving the explored challenges are proposed. In conclusion, the integration of BC with IoT could produce promising results in enhancing the security and privacy of IoT environment.